Decolonising the school curriculum in an era of political polarisation. (10th August 2022) - Akhter, Shahnaz; Watson, Matthew
Abstract : Recent consciously curated conditions of political polarisation have prevented English schools from taking even the first tentative steps towards decolonising the curriculum. Since returning to power in 2010, successive Conservative Secretaries of State for Education have resolved to restore traditional learning methods to English classrooms, championing the need for children to passively accept content chosen for them by government appointees who are answerable to political rather than to pedagogical priorities. This had already created an unsupportive political environment for transforming what children might learn, before such difficulties were magnified following the Brexit referendum of 2016. Decolonisation has increasingly been identified by Conservative Party strategists as one of their beloved wedge issues, something that can be used to stoke electorally expedient anger against 'the Remainer elite' among Leave-voting communities. Hopes for a serious debate about the principles of decolonisation were frustrated by the Johnson government hijacking the very mention of the word to use as evidence that the 'woke' brigade was running hopelessly out of control. The case for decolonising the English school curriculum has been subjected to a full-frontal populist culture-war attack on an educational establishment accused of refusing to allow children to see the good in their country.